Uso De Derive Y Su Incidencia En El Proceso Enseñanza - Aprendizaje En El Calculo De Gráficas De Transformadas De Fourier En Matematica - Marcelo, Coronel Maji Franklin; Rodrigo, Guilcapi Mosquera Jaime; Hernán, Torres Rodríguez Klever (European Scientific Journal, ESJ, 2018)
The aim of this the research was to determine the incidence of DERIVE use in the teaching-learning process of Fourier transform graphs calculation in Mathematics 1 subject. For this, it was necessary to consider the Network and Telecommunications Electronics Engineering School first level students of Escuela Superior Politécnica de Chimborazo as a sample. This research is descriptive, quasi-experimental and deductive- hypothetical. The sample of the research is intentional and it considered two groups: the control group that represents the traditional method with 42 students and the experimental group to which an intervention plan using DERIVE with 35 students was applied. The two groups were evaluated into two scenarios before and after the intervention (Pre and Post) through a rubric that evaluated the activities contained in the syllabus of the subject. The data obtained represent the academic performance achieved by the students of each group, these data were tabulated, analyzed, interpreted and finally put under a Z statistical test, which determined that the use of DERIVE influences positively in the teaching-learning process of Fourier transform calculation in Mathematics.